2022
DOI: 10.1088/2053-1591/ac4d54
|View full text |Cite
|
Sign up to set email alerts
|

Effect of low-velocity impact on mechanical property and fatigue life of DP590/AA6061 self-piercing riveted joints

Abstract: The low-velocity impact behaviors of DP590/AA6061 self-piercing riveting (SPR) joints are studied at the impact energies of 5 J, 10 J, 20 J, 30 J, and room temperature (25℃). The lap shear and fatigue tests, and the cross-sectional microscopies of joints are used to assess the mechanical property evolutions of the joints after low-velocity impact. The results show that the absorbed impact energies of SPR joints reach the critical value at an impact energy of 30 J, the exceeded impact energy causes crack failur… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
3
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7

Relationship

3
4

Authors

Journals

citations
Cited by 9 publications
(9 citation statements)
references
References 39 publications
(44 reference statements)
0
3
0
Order By: Relevance
“…However, due to the complicated forming and heating process, the cost of AA7075 and AA2024 alloys is relatively high, which is not the ideal section for the automobile industry. Due to the higher cost-performance, light weight and good plasticity, the AA6061 aluminum alloy is extensively used in multi-material design of body-in-white and aircraft [8,9]. Self-piercing riveting (SPR) is a new deformation connection technology.…”
Section: Introductionmentioning
confidence: 99%
“…However, due to the complicated forming and heating process, the cost of AA7075 and AA2024 alloys is relatively high, which is not the ideal section for the automobile industry. Due to the higher cost-performance, light weight and good plasticity, the AA6061 aluminum alloy is extensively used in multi-material design of body-in-white and aircraft [8,9]. Self-piercing riveting (SPR) is a new deformation connection technology.…”
Section: Introductionmentioning
confidence: 99%
“…The main sources of impact wear on the SPR joints come from the impact of stones or gravel, hail, and raindrops during the driving of the automobile [9]. The speed of this type of impact breakage is usually between 1 and 10 ms −1 , and it is often referred to as the low-speed impact [9][10][11]. Generally, the low-speed impact wear causes a minimal effect on component surface quality.…”
Section: Introductionmentioning
confidence: 99%
“…In particular, the residual tensile strength [22,23], residual flexural strength [24,25], residual fatigue life [26,27], and residual kinetic properties [28] of impact-damaged composite laminates are investigated. Zhao et al [9] studied the impact behavior of self-piercing riveted joints made of dissimilar materials (DP590/AA6061) at impact energies of 5 J, 10 J, 20 J, and 30 J, and the results show that low-speed impact does not change the tensile failure mode of the joint, but significantly reduces its mechanical self-locking performance. Khoramishad et al [29] studied the effect of stacking order on the low-speed impact behavior of metal laminates, and revealed that the impact performance of metal laminates is mainly influenced by the number of metal layers and the material properties of the first and last metal layers.…”
Section: Introductionmentioning
confidence: 99%
“…These materials need to be connected. Self-Piercing Riveting (SPR) technology can effectively realize the connection of lightweight materials, and is widely used in production [ 3 , 4 , 5 , 6 ].…”
Section: Introductionmentioning
confidence: 99%